EXPERIMENTAL CHARACTERISATION OF THE STIFFNESS AND LEAKAGE OF A PROTOTYPE LEAF SEAL FOR TURBINE APPLICATIONS - Jahn, I; Owen, A; Franceschini, G; Gillespie, D; ASME (2008)
The leaf seal, a seal comprising multiple flexible elements, offers similar leakage to a brush seal, but may have other benefits that make it a more attractive option in some applications. This paper details an experimental investigation of the leakage and stiffness of a pair of prototype leaf seals carried out in a slow speed rotating rig at differential pressures of up to 0,4 MPa. The stiffness is characterised by measuring the force required to create excursions of the housing relative to the seal. The results are presented in terms of the effective annular clearance of an idealised labyrinth seal. For a single seal design, in which contact between the leaf tips causes inherent damping in the seal, the effect of changes in seal housing geometry are reported. The results observed are explained with reference to the flow field in the leaf pack. Copyright © 2008 by ASME.